Religious Moderation and Community Cohesion: Exploring Social Memory, Identity, and Solidarity in the Phu Khao Thong Muslim Community, Ayutthaya - Liu, Yaoping; Rakthin, Chatchai; Budianto, Langgeng (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2025)
This research explores the interplay of social memory, identity, and social solidarity in the Muslim community in Thailand. The research uses an exploratory sequential mixed-method design. First, a total of 150 participants were involved in the quantitative approach which obtained through an online survey and Structural Equation Modeling (SEM) to test the research hypotheses. The second stage involved interviews with fithteen Muslim community leaders to investigate how individual and collective practices contribute to preserving the community's identity, tolerance and social memory. The findings reveal that social solidarity, reflected in mosque gatherings, cultural events, mutual support systems, and collective economic initiatives, is crucial in preserving tolerance, social memory and reinforcing communal identity. Solitary religious practices, like prayer and reflection, enhanced individual connections to the community's history, while participation in communal activities strengthened shared identity. The Muslim community leaders identified the mosque as a religious centre and a hub for transmitting historical knowledge and fostering religious moderation and social cohesion. This result extending the understanding of how social memory and identity are maintained in Thai Muslim communities, particularly minority groups like Phu Khao Thong. Particularly in light of modernisation and evolving socio-economic conditions globally.